Unmanaged Drinking Water Sources in Arid Areas of Rajasthan : A Case Study of Nagaur District - Chattergi, P C; Vangani, N S; Sharma, M L (Annals of Arid Zone, 2016)
The study on the quality of drinking water in Nagaur district revealed several types of water-borne diseases viz., stomach disorder, deformation of bones, guineaworm infestation and other infectious diseases especially in the villages using tank water. Deformation of bones and stomach disorders were more common in the villages mostly dependent on groundwater. The ground water was also found to have high total soluble salts, sulphate, nitrate, chloride and fluoride contents. It emerges from this case study that a major percentage of the inhabitants do not receive potable and safe drinking water. Hence, some measures to overcome these health problems associated with drinking water sources have been suggested.